Elderly Screening and Education about Hypertension in Padang City - Bun Yurizali; Nurmaines Adhyka (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Hypertension is a complex problem that can affect anyone over the age of 18. The problem of hypertension is still a world problem with the increasing population prevalence every year. Complications of hypertension can cause various diseases that lead to death. There are so many people who still do not know how to face this disease along with the risk factors. In society nowadays, a lot of misperceptions and myths the spread widely about this disease. Therefore, the author provides socialization regarding hypertension to the elderly from the Indonesian Catholic Women's Association. This activity was carried out for one day with 60 participants of various ages, with a range up to 81 years. Activities in the form of socialization, question and answer, and discussion which closed with blood pressure measurement. Seeing the enthusiasm of the participants even though they came from the elderly shows that there is a need to carry out routine socialization regarding health and promote regular health checks for the elderly in this organization in a wider coverage area